Assessment of sleep quality and its predictors among patients with diabetes in Jazan, Saudi Arabia - Darraj A (Dove Medical Press, 2018)
Abdulaziz Darraj,1 Mohamed Salih Mahfouz,2 Abdullah Alsabaani,3 Mubarack Sani,2 Anwar Alameer1 1Jazan Health Affairs, Ministry of Health, Jazan, Saudi Arabia; 2Family and Community Medicine Department, College of Medicine, Jazan University, Jazan, Saudi Arabia; 3Family and Community Medicine Department, College of Medicine, King Khalid University, Abha, Saudi Arabia Background: Poor sleep quality is common among patients with diabetes. It is associated with negative physical, psychological, and functional consequences. However, the implicated risk factors of poor sleep quality remain uncertain.Objectives: This study aimed to determine the prevalence of poor sleep quality among patients with diabetes and to investigate the factors associated with the poor sleep quality.Patients and methods: An analytical cross-sectional study of 307 diabetic patients in Jazan, Saudi Arabia was conducted in 2018. A multistage cluster random sampling was used to select the study participants. Sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI). Data on patient’s characteristics were gathered via patients’ interviews, and medical data were collected based on the patients’ files. Logistic regression analysis was used to identify the predictors of poor sleep quality.Results: The mean score of PSQI was 5.29±2.73. The prevalence of poor sleep quality was 55.4% (95% CI 49.7–60.8). Sociodemographic and clinical factors were significantly associated with poor sleep quality, such as being elderly, female, illiterate, smoker, complications of diabetes, comorbidity, or psychological symptoms. However, female gender was the strongest predictor of reporting poor quality of sleep, OR= 3.69, 95% CI 1.65–8.28 (P<0.001).Conclusion: Poor sleep quality among diabetic patients is a prevalent health problem. Many factors can affect sleep quality. Health care providers may consider routine screening for and address sleep problems among diabetic patients. Keywords: poor sleep quality, prevalence, risk factors, diabetes mellitus, Saudi Arabia